PENERIMAAN DOSIS ORGAN KRITIS PADA PEMERIKSAAN CEREBRAL DSA DENGAN BIPLANE C-Arm - Adelina Oinike; Guntur Winarno; Purwatinigsih Purwatinigsih (Perhimpunan Radiografer Indonesia (PARI), 2020)
Background:Cerebral Digital Substraction Angiography (DSA) screening is widely used in hospitals to find out even treat strokes and vascular abnormalities. During the examination, the patient received radiation from a C-Arm Biplane. The estimated dose received by the patient has been measured on the monitor screen which is the DAP value, but to find out the actual dose received by the patient, it is necessary to measure directly using the TLD attached to the patient's body during the examination. Method: Measurement of critical organ dose is done by attaching TLD-100 chips on the surface of the eye, thyroid, and gonad to 6 different patients. Results: The purpose of this study was to measure and evaluate the amount of dose received by the patient's critical organs during Cerebral DSA examination. Conclusion: The results showed that (1) the amount of eye dose received by the patient during cerebral DSA examination was 23.01 mGy to 144,787 mGy. (2) the amount of thyroid dose received by the patient during cerebral DSA examination is 15,348 mGy to 76,162 mGy. (3) the amount of gonad dose received by the patient during Cerebral DSA examination is 0.09 mGy to 229,848 mGy. (4) DAP values during Cerebral DSA examination obtained values in the range of 77088 mGycm2 to 167718 mGycm2.